Above and beyond emotional valence: The unique contribution of central and traumatic shame memories to psychopathology vulnerability - Matos, Marcela (2012)
This paper explores whether shame memories have a distinct impact on emotional difficulties and psychopathology that goes beyond their negative emotional valence. Study 1 (N=292) investigates the contribution of centrality of shame memory, in comparison to the centrality of fear and sadness memories, to explain the memory's traumatic impact, shame, depression, anxiety, stress, paranoid, and dissociative symptoms. Study 2 (N=192) explores the impact of shame traumatic memory on shame and depression, anxiety, and stress symptoms, in comparison to fear and sadness traumatic memories. Both studies used undergraduate student samples. Results show that shame memories' centrality and traumatic features made an independent contribution to current external and internal shame and distinct psychopathological symptoms, after controlling for the effect of fear and sadness, centrality, and traumatic qualities. Moreover, shame memories' centrality and traumatic features were the best global predictors of external and internal shame and depressive symptoms. Centrality of shame memories was also the only significant predictor of paranoid ideation and dissociation. These results offer novel perspectives on the nature of shame and its relation to psychopathology, emphasising the distinct role of shame memories in human functioning and suffering, which goes above and beyond its negative emotional valence.